2016
DOI: 10.1007/s13353-016-0360-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic correlation estimates between beef fatty acid profile with meat and carcass traits in Nellore cattle finished in feedlot

Abstract: The objective of this study was to estimate the genetic-quantitative relationships between the beef fatty acid profile with the carcass and meat traits of Nellore cattle. A total of 1826 bulls finished in feedlot conditions and slaughtered at 24 months of age on average were used. The following carcass and meat traits were analysed: subcutaneous fat thickness (BF), shear force (SF) and total intramuscular fat (IMF). The fatty acid (FA) profile of the Longissimus thoracis samples was determined. Twenty-five FAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 51 publications
0
15
1
11
Order By: Relevance
“…However, estimates of parameters of genetic or genetic variability within breeds for fatty acid composition have been widely studied. Currently, the availability of genomic data for selection of traits associated with meat quality and lipid profile in cattle has increased [103], since there is a collection of information by research institutions, especially in Nellore herds [32,35,37,104].…”
Section: Genetic Factor That Influence the Fatty Acid Compositionmentioning
confidence: 99%
“…However, estimates of parameters of genetic or genetic variability within breeds for fatty acid composition have been widely studied. Currently, the availability of genomic data for selection of traits associated with meat quality and lipid profile in cattle has increased [103], since there is a collection of information by research institutions, especially in Nellore herds [32,35,37,104].…”
Section: Genetic Factor That Influence the Fatty Acid Compositionmentioning
confidence: 99%
“…Studies have shown that in feedlot finishing systems, Bos taurus meat presents lower percentages of SFA, higher percentages of MUFA, and similar levels of PUFAs compared to Bos indicus meat (Perry, Nicholls, & Thompson, 1998;Menezes et al, 2009;Rossato et al, 2010;Bressan et al, 2011). According with Feitosa et al (2016) who worked with the same data set used in this study, the mean ± SD values for shear force (5.17 ± 1.4), intramuscular fat content (0.82 ± 0.42%) and back fat thickness (4.02 ± 2.7 mm) indicated that the beef acceptability could compromised in some international markets. However, the Nellore beef has attributes that are beneficial to human health such as low intramuscular fat content and a beef fatty acid profile with high levels of the n-3 series and an adequate dietary quality based on the n-6/n-3 and PUFA/SFA ratios.…”
Section: Fatty Acid Profilementioning
confidence: 99%
“…On this concern, some studies have been done to estimate these parameters. In these sense, Feitosa et al [37] studied the genetic-quantitative relationships between the beef faty acid proile with the carcass and meat traits of Nelore catle used a total of 1826 bulls inished in feedlot conditions to analyze the following carcass and meat traits: subcutaneous fat thickness (BF), shear force (SF), and total intramuscular fat (IMF). The faty acid (FA) proile of the longissimus thoracis samples was determined.…”
Section: Meat Faty Acids Proile Variation Between and Within Beef Catmentioning
confidence: 99%